SOCIO-PSYCHOLOGICAL ASPECTS IN ECO ETHICS IN ENGLISH LITERATURE - Yasoda, S. Mazhali (International Journal of Psychosocial Rehabilitation, 2020)
Ecocriticism is a kind and congenial mediation between human and non- human worlds. Thus, the theory of Ecocriticism refers to the study of the relationship between literature and environment. Since prehistory, literature and the arts have been drawn to renders of physical environment and human environment interactions. Nowadays the literary critics pay surveillance on study and analysis of the strong bond between nature and society. Ecology and Eco criticism are the consequential aspects for the literary study and research. CherylGlotfelty’s working definition in the Eco criticism reader is that “Eco criticism” is the study of the relationship between literature and physical environment, and one of the implicit goals of the approach is to recoup professional dignity for what Glotfelty calls the “undervalued genre of nature writing”. Literature in the present world has become a multidisciplinary arena. Now literature is a penetrative integration of geopolitics, economics, philosophy, anthropology and so on. Approaching literature from an ecological perspective is known as Eco criticism. In Peter Barry’s Beginning theory, it has also been referred to as “green studies”. Natural environment has been focused on by a large number of authors, poets and playwrights belonging to previous as well as current eras in both metaphoric and literal ways. A literary work becomes all the more moving and explicit when it interlinks ecological phenomena and environmental resources with its plot, characters and thematic concerns keeping this in view, we can refer to AmitavGhosh’sThe Hungry Tide, Chinua Achebe’s Things Fall Apart and Joseph Conrad’s Heart of Harkness as ideal works of fiction to be appraised in light in Eco criticism.